2014
DOI: 10.1016/j.pharmthera.2013.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Gene and protein therapies utilizing VEGF for ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that is usually fatal within 2–5 years. Unfortunately, the only treatment currently available is riluzole, which has a limited efficacy. As a redress, there is an expanding literature focusing on other potential treatments. One such potential treatment option utilizes the vascular endothelial growth factor (VEGF) family, which includes factors that are primarily associated with angiogenesis but are now increasingly recognized to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 138 publications
(127 reference statements)
1
38
0
Order By: Relevance
“…We choose common neurotrophic factors, including bFGF and VEGF, and surveyed their differences between ALS patients and control subjects. VEGF is associated with angiogenesis and has recently been shown to exert neurotrophic effects on neurons (Keifer, O'Connor, & Boulis, 2014); a similar trophic effect was also found with bFGF (Chen, Cai, Shen, Cai, & Lei, 2014). We measured increased bFGF and VEGF levels in both the CSF and serum and noted positive correlations with disease duration but negative associations with DPR.…”
Section: Discussionmentioning
confidence: 81%
“…We choose common neurotrophic factors, including bFGF and VEGF, and surveyed their differences between ALS patients and control subjects. VEGF is associated with angiogenesis and has recently been shown to exert neurotrophic effects on neurons (Keifer, O'Connor, & Boulis, 2014); a similar trophic effect was also found with bFGF (Chen, Cai, Shen, Cai, & Lei, 2014). We measured increased bFGF and VEGF levels in both the CSF and serum and noted positive correlations with disease duration but negative associations with DPR.…”
Section: Discussionmentioning
confidence: 81%
“…A recently published study demonstrated that microRNA‐containing exosomes derived from maternal and umbilical cord serum dramatically promote human umbilical vein endothelial cell proliferation, migration, and tube formation in vitro, highlighting the important role of exosomes in the regulation of angiogenesis during gestation. Exclusively, VEGF has been studied for potential therapeutic efficacy in animal models of ALS and its use in clinical settings has been discussed (reviewed). Nevertheless, CBP containing high levels of IL‐8 and VEGF might be a beneficial treatment for repair of the damaged blood–brain barrier and/or blood–spinal cord barrier in patients with ALS, AD, Parkinson's disease and multiple sclerosis …”
Section: Discussionmentioning
confidence: 99%
“…In our current analysis of transgenic SOD1 G93A mouse spinal cord and muscle tissue, we detected no significant difference in VEGF mRNA expression between mutant SOD1 G93A and wildtype animals. Previous studies have consistently shown positive effects of treatment with VEGF on motor function and survival in ALS animal or in vitro models (Dewil et al, 2007;Dodge et al, 2010;Keifer, O'Connor, & Boulis, 2014;Lemmens et al, 2007;Li, Xu, Luo, Gozal, & Liu, 2003;Pronto-Laborinho et al, 2014;Storkebaum et al, 2005;Zheng, Nennesmo, Fadeel, & Henter, 2004). Increased Nrp1 expression in spinal cord tissue might therefore represent a regulatory mechanism to enhance VEGF effects.…”
Section: Discussionmentioning
confidence: 96%